Digital Circuit Projects An Overview of Digital Circuits Through Implementing Integrated Circuits - Kann, Charles W. (Open textbook library., 2014)
Digital circuits, often called Integrated Circuits or ICs, are the central building blocks of a Central Processing Unit (CPU). To understand how a computer works, it is essential to understand the digital circuits which make up the CPU. This text introduces the most important of these digital circuits; adders, decoders, multiplexers, D flip-flops, and simple state machines. What makes this textbook unique is that it puts the ability to understand these circuits into the hands of anyone, from hobbyists to students studying Computer Science. This text is designed to teach digital circuits using simple projects the reader can implement. But unlike most lab manuals used in classes in Digital Circuits or Computer Organization classes, this textbook is designed to remove the barrier of a laboratory infrastructure needed in a face-to-face environment at a college or university. This textbook is designed to be used by the reader to create the circuits in their own homes. The textbook is free. The cost of the kits needed to do the labs is reasonable. And the projects are well documented and can be implemented by even novices to electronic projects. This text allows professors to add laboratory projects in digital circuits to students in online classes in Computer Organization. This enhances these classes with interesting and fun exercises that reinforce the classroom topics. This text can also be used by a hobbyist who wants to learn more about digital circuits and how computers work. The material is presented at a level that someone with no experience in digital circuits and electronics can successfully complete the projects, and gain an understanding of the circuits which go into making up a computer.